Growing Together, Empowering Together: Building Food Security from the Village - Putu Indah Budi Apsari; Mirah Sastradiyadnya Suwitra (Lembaga Pengabdian Kepada Masyarakat, Universitas Warmadewa, 2025)
Food issues are quite complex and complicated in society. People spend 70% of their income to meet food needs. Through the KKN-PMM Warmadewa University in Sibang Gede Village, we raised this issue to be targeted in the village food security system strengthening program. Our purpose hoped that this food security program will produce healthy food sources for the community. The activities carried out include planting long bean seedlings and raising catfish. The results of this community service have produced long bean plants 10 cm tall and 48 catfish. The sustainability of this program will be monitored by the village team. The long beans will be raised by the local community and the catfish will be given to the underprivileged.